From Regulation to Transparency: Policy Implementation of Public Information Disclosure in Indonesian State Religious Universities within the SDG 16 Framework - Iswantoro; Tobroni, Faiq; Aktar, Md Nadim (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2025)
Public information disclosure is a cornerstone of transparent, accountable, and participatory governance in higher education. This study examines the implementation of public information disclosure (PID) in State Religious Higher Education Institutions (PTKN) under Law No. 14/2008 and its derivative regulations. It aims to identify the gap between regulatory frameworks and institutional practices and to propose strategies for optimizing disclosure. The analysis employs Mazmanian’s policy implementation theory, focusing on three dimensions: problem characteristics, policy characteristics, and external environment. Data were drawn from the 2024 Monitoring and Evaluation (Monev) conducted by the Central Information Commission, complemented by a review of regulatory instruments and institutional practices in PTKN. The results indicate that most PTKN are still categorized as “less informative” or “non-informative.” Implementation barriers include limited administrative capacity, inadequate digital infrastructure, weak monitoring systems, and entrenched bureaucratic cultures. These factors collectively prevent PTKN from fully realizing the objectives of the Public Information Disclosure Law.The study proposes strategies to overcome these barriers, including enhancing the competence of Information and Documentation Management Officers (PPID), developing integrated digital platforms, strengthening leadership commitment, and institutionalizing rigorous monitoring and evaluation mechanisms. Collaboration with external stakeholders and improved public literacy on the right to information are also essential. Optimizing PID is not only a matter of legal compliance but also a governance tool and a moral responsibility aligned with religious values. Successful implementation will enhance public trust, institutional accountability, and the global relevance of Indonesia’s religious higher education sector while contributing to Sustainable Development Goal (SDG) 16.